Власні взаємні паразитні параметри елементів протизавадних фільтрів для джерел електроживлення ключового типу - Гурін, В.К.; Павловський, В.О.; Юрченко, О.М. (Технічна електродинаміка, 2012)
It is showed that there are two types of parasitic parameters in circuits of power line filters: self-parasitics and mutual parasitics. It is showed the basic essence of those parameters and their influence on filters’ insertion loss.